2021
DOI: 10.1136/bcr-2020-238055
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of CPAP in a pregnant patient with COVID-19 pneumonia

Abstract: A 35-year-old nurse, who was 27 weeks pregnant at the time, was admitted to hospital with a short history of cough, fever and worsening shortness of breath. Oral and nasopharyngeal swabs were positive for SARS-CoV-2 on real-time viral PCR. During her admission, her breathing further deteriorated and she developed type 1 respiratory failure. A decision was made to trial treatment with continuous positive airway pressure (CPAP) as a means of avoiding intubation. The patient tolerated this well and made rapid imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Prior studies have reported the efficacy of h-CPAP in improving oxygenation in patients with community acquired pneumonia and moderate hypoxemic ARF when compared to standard oxygen therapy [ 11 ]. A recent case report has showed the feasibility of h-CPAP application also in a pregnant woman with SARS-CoV-2 pneumonia and hypoxemic ARF, however no direct comparison between ABG values before and during h-CPAP application was available [ 9 ]. Therefore, our study is the first to describe the effect of h-CPAP on ABG values in pregnant women with SARS-CoV-2 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have reported the efficacy of h-CPAP in improving oxygenation in patients with community acquired pneumonia and moderate hypoxemic ARF when compared to standard oxygen therapy [ 11 ]. A recent case report has showed the feasibility of h-CPAP application also in a pregnant woman with SARS-CoV-2 pneumonia and hypoxemic ARF, however no direct comparison between ABG values before and during h-CPAP application was available [ 9 ]. Therefore, our study is the first to describe the effect of h-CPAP on ABG values in pregnant women with SARS-CoV-2 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both the PEEP non-responder women required ETI. A recent summary of available evidence reported only one case of worsening of respiratory failure requiring escalation to IMV out of 18 cases of pregnant women with COVID-19 requiring non-invasive ventilation [ 9 ]. Given the paucity of cases described so far, it is impossible to draw definitive conclusions on the efficacy of h-CPAP in preventing ETI in pregnant women and on the prognostic role of PEEP responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently and with increased experience, the use of intermediate therapies has gained favor, including noninvasive positive-pressure ventilation with bilevel positive airway pressure, continuous positive airway pressure, and high flow nasal cannula, having now been employed successfully in obstetric patients. 34 Prone positioning, 35 – 39 high concentration nitric oxide inhalation, 40 and extracorporeal membrane oxygenation (ECMO) are further successful therapeutic options once mechanical ventilation has been established. 41 51 …”
Section: Introductionmentioning
confidence: 99%
“…Oxygen supplementation with nasal oxygen therapy or tracheal intubation were initially proposed as the 2 modalities for COVID-19 management in pregnant people, with other in between modalities initially not employed to reduce the risk of aerosolization, and because it was thought that rapid escalation to invasive mechanical ventilation would be needed. Subsequently and with increased experience, the use of intermediate therapies has gained favor, including noninvasive positive-pressure ventilation with bilevel positive airway pressure, continuous positive airway pressure, and high flow nasal cannula, having now been employed successfully in obstetric patients 34. Prone positioning,35–39 high concentration nitric oxide inhalation,40 and extracorporeal membrane oxygenation (ECMO) are further successful therapeutic options once mechanical ventilation has been established 41–51…”
Section: Introductionmentioning
confidence: 99%